Effervescent Tablet with Lime Peel and Tamarind Extract as Fruit and Vegetable Decontaminants - Zelly Salmiyanti Rahman Zam; Novia Elsaputri; Farah Alya Amril; Fathiya Rizqillah Ranza; Najla Khalisha Alem; Zuhrah Taufiqa (CV. AFDIFAL MAJU BERKAH, 2026)
The safety of fruits and vegetables is important to prevent diseases caused by contamination by pathogenic microbes such as Escherichia coli and Staphylococcus aureus. This study aims to formulate and test the antimicrobial activity of effervescent effervescentes based on lime (Citrus aurantifolia) and tamarind (Tamarindus indica) peel extracts as natural decontaminants. The study was conducted experimentally with a post-test only design in the Integrated Laboratory and Biomedical Laboratory of the Faculty of Medicine, Padang State University. Effervescent tablets were made by the wet effervescentation method using three variations of extract concentrations (7%:5%), (6%:6%), and (5%:7%). The antimicrobial activity was tested against Escherichia coli and Staphylococcus aureus using the disc diffusion method on MHA media. The results showed that the extracts contain flavonoids, tannins, and organic acids that act as antimicrobial agents. The three formulations produced different inhibition zones, with formula 1 (7%:5%) effective against Escherichia coli (7.5 mm) and formula 3 (5%:7%) effective against Staphylococcus aureus (13 mm). The effervescent tablet had a dissolution time of <2 minutes.